Stepwise activation of hemimorphite surfaces with lead ions and its contribution to sulfidization flotation - Yi, Yahui; Li, Peixuan; Zhang, Ga; Feng, Qicheng; Han, Guang (Separation and purification technology, 2022)
[Display omitted] •Stepwise activation with Pb2+ improved the floatability of hemimorphite.•Stepwise activation with Pb2+ was beneficial in promoting the surface sulfidization of hemimorphite.•The content of highly active lead sulfide species on hemimorphite surfaces was increased after stepwise activation.•The surface hydrophobicity of hemimorphite was enhanced after stepwise activation. The surface activity of hemimorphite is poor; therefore, it is difficult to efficiently sulfidize the hemimorphite surface. Herein, stepwise addition of lead ions (Pb2+) was shown to be effective for increasing the content of active sites on the hemimorphite surface. The activation mechanism of hemimorphite by Pb2+ and its effect on flotation were investigated by microflotation experiments and surface analysis. The microflotation results indicated that stepwise activation with Pb2+ dramatically improved the flotation behavior of hemimorphite compared with single-stage activation. The results of time-of-flight secondary-ion mass spectrometry and X-ray photoelectron spectroscopy showed that stepwise activation with Pb2+ increased the activity of sulfidization products on the hemimorphite surface. This facilitated the generation of highly active lead sulfide species and created favorable conditions for subsequent interaction of xanthate with the mineral surface. The results of infrared spectroscopy and contact-angle analysis indicated that stepwise activation with Pb2+ enhanced the xanthate adsorption on hemimorphite surfaces, and a strongly hydrophobic surface was obtained. Accordingly, the flotation recovery of hemimorphite increased after stepwise activation with Pb2+, which provided a new idea and method for efficient recycling of zinc resources from complex and refractory zinc oxide ores.